Measurement of the top quark mass using the matrix element technique in dilepton final states - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (Amer Physical Soc, 2016)
We present a measurement of the top quark mass in p (p) over bar collisions at a center-of-mass energy of 1.96 TeV at the Fermilab Tevatron collider. The data were collected by the D0 experiment corresponding to an integrated luminosity of 9.7 fb(-1). The matrix element technique is applied to t (t) over bar events in the final state containing leptons (electrons or muons) with high transverse momenta and at least two jets. The calibration of the jet energy scale determined in the lepton + jets final state of t (t) over bar decays is applied to jet energies. This correction provides a substantial reduction in systematic uncertainties. We obtain a top quark mass of m(t) = 173.93 +/- 1.84 GeV.